2016
DOI: 10.1242/dev.133652
|View full text |Cite
|
Sign up to set email alerts
|

Heartbreak hotel: a convergence in cardiac regeneration

Abstract: In February 2016, The Company of Biologists hosted an intimate gathering of leading international researchers at the forefront of experimental cardiovascular regeneration, with its emphasis on 'Transdifferentiation and Tissue Plasticity in Cardiovascular Rejuvenation'. As I review here, participants at the workshop revealed how understanding cardiac growth and lineage decisions at their most fundamental level has transformed the strategies in hand that presently energize the prospects for human heart repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“… 78 While initially reported results appeared promising, subsequent research indicated that most infused MSCs were trapped in the lungs and swiftly eliminated by the host immune system, instead of being successfully engrafted. 79 , 80 The therapeutic benefits, if existed, might be attributed to the MSCs-secreted cytokines and other trophic factors—which can function in anti-inflammation, angiogenesis, and immune modulation—rather than the direct differentiation and regenerative capacities of the cells themselves. 81 Therefore, it is increasingly clear that providing a supportive platform for transplanted stem cells to sustain their viability, improve their retention, and shield them from immune attacks is crucial for successful engraftment and leveraging their differentiation and regenerative potential.…”
Section: Hydrogels For Cell Therapymentioning
confidence: 99%
“… 78 While initially reported results appeared promising, subsequent research indicated that most infused MSCs were trapped in the lungs and swiftly eliminated by the host immune system, instead of being successfully engrafted. 79 , 80 The therapeutic benefits, if existed, might be attributed to the MSCs-secreted cytokines and other trophic factors—which can function in anti-inflammation, angiogenesis, and immune modulation—rather than the direct differentiation and regenerative capacities of the cells themselves. 81 Therefore, it is increasingly clear that providing a supportive platform for transplanted stem cells to sustain their viability, improve their retention, and shield them from immune attacks is crucial for successful engraftment and leveraging their differentiation and regenerative potential.…”
Section: Hydrogels For Cell Therapymentioning
confidence: 99%
“…Some promising therapies that used systemically injected cells to treat myocardial infarction were initially thought to act by engraftment and differentiation to replace damaged host cardiac tissue. However, further investigation revealed that the cells did not in fact engraft but were rapidly cleared by the host immune system 40 , 41 , and that tissue regeneration was instead accomplished by immunogenic and tissue-genic factors secreted by the MSCs 42 . Unfortunately, inconsistent results in subsequent clinical trials resulted in failure to commercialize these therapies, underscoring how challenges of uncharacterized mode of action, inconsistent potency and poor in vivo viability can hamper MSC translation 43 .…”
Section: Progress and Challenges In Cell-based Therapymentioning
confidence: 99%